Protocol proposal for obtaining organic fertilizer from microalgas (Agroindustria, Sociedad y Ambiente, 2020)
The use of biofertilizers constitutes an alternative for the sustainable management of soils and the fertilization of crops, considering the contribution of macro and micronutrients essential for the development of the plants, their use would allow minimizing the production costs and reducing the environmental impact caused by the excessive use of chemical fertilizers. Based on this, the use of Chlorella sp. and Scenedesmus sp for the production of biofertilizers, for this the chemical characterization of the microalgae was carried out, for which the parameters pH, EC, content of the macronutrients N, P, K, Ca, Mg, S and micronutrients B were determined, Zn, Cu Fe and Mn. The results obtained show that the microalgae have a high potential as a fertilizer due to the high nutrient content, however there is currently no methodology for efficient use at the field or greenhouse level, so a protocol for propagation, isolation is proposed, massification, scaling and use of a biofertilizer based on Chlorella sp and Scenedesmus sp.
Keywords: Biofertilization; mineral nutrition; microorganisms; sustainability